Strategi Human Resource dalam Pengembangan Kompetensi Digital dan Teknologi Prediktif pada Tenaga Kerja Divisi Produksi Sektor MRO di Kota Bandung - Budiarti, Isniar (JEMBA, 2025)
The rapid development of digital transformation in the Maintenance, Repair, and Overhaul (MRO) sector requires human resource (HR) strategies that are adaptive to technological advancements. This study aims to analyze HR strategies in developing digital competencies and the readiness to adopt predictive technologies among production employees in the MRO sector in Bandung. A descriptive quantitative method was employed through questionnaires, observations, and documentation. The findings indicate that employees’ digital competencies fall into a good category, supporting their readiness for digital transformation. However, the implementation of predictive technology remains limited and has not yet been optimized to support real-time machine performance prediction. HR strategies implemented include technical training on digital tools, the use of maintenance software, and internal digital literacy programs. Furthermore, predictive technology development focuses on needs-based training in machine learning and data analysis. These findings highlight the strategic role of HR in strengthening workforce competencies and accelerating digital transformation in the MRO production sector